Plant Growth-Promoting Rhizobacteria Enhance Defense of Strawberry Plants Against Spider Mites - Hosseini, Afsane; Hosseini, Mojtaba; Schausberger, Peter (Frontiers in Plant Science, 2022)
Plants mediate interactions between below- and above-ground microbial and animal communities. Microbial communities of the rhizosphere commonly include mutualistic symbionts such as mycorrhizal fungi, rhizobia and free-living plant growth promoting rhizobacteria (PGPR) that may influence plant growth and/or its defense system against aboveground pathogens and herbivores. Here, we scrutinized the effects of three PGPR, Azotobacter chroococcum, Azospirillum brasilense and Pseudomonas brassicacearum, on life history and population dynamics of two-spotted spider mites, Tetranychus urticae, feeding on aboveground tissue of strawberry plants, and examined associated plant growth and physiology parameters. Our experiments suggest that these three species of free-living rhizobacteria strengthen the constitutive, and/or induce the direct, anti-herbivore defense system of strawberry plants. All three bacterial species exerted adverse effects on life history and population dynamics of T. urticae and positive effects on flowering and physiology of whole strawberry plants. Spider mites, in each life stage and in total, needed longer time to develop on PGPR-treated plants and had lower immature survival rates than those fed on chemically fertilized and untreated plants. Reduced age-specific fecundity, longer developmental time and lower age-specific survival rates of mites feeding on rhizobacteria treated plants reduced their intrinsic rate of increase as compared to mites feeding on chemically fertilized and control plants. The mean abundance was lower in spider mite populations feeding on PGPR-treated strawberries than in those feeding on chemically fertilized and untreated plants. We argue that the three studied PGPR systemically strengthened and/or induced resistance in above-ground plant parts and enhanced the level of biochemical anti-herbivore defense. This was probably achieved by inducing or upregulating the production of secondary plant metabolites, such as phenolics, flavonoids and anthocyanins, which were previously shown to be involved in induced systemic resistance of strawberry plants. Overall, our study emphasizes that PGPR treatment can be a favorable strawberry plant cultivation measure because providing essential nutrients needed for proper plant growth and at the same time decreasing the life history performance and population growth of the notorious herbivorous pest T. urticae.